Relationship Between Quality Of Sibling Relationship And Personality Traits Among Single Parent Families - Maryam Kausar , Aneela Begum , Allah Nawaz , Wakqas Khalid Ally , Ishtiaq Ahmad Awan , Sonia niazi , Afroz Ahmad (Migration Letters, 2024)
Objectives: This study’s main focus was to explore how the quality of sibling relationships relates to the personality traits of individuals in single-parent families. Sample description: The sample comprises 200 adults (100 from single-family structures, 100 from intact family structures), ages 20-30, from district Swabi. Measures: The demographic sheet, Life Span Sibling Relationship Scale (Riggio, 2000), and Big Five Inventory (BFI) (John & Srivastava, 1999) were utilized for data collection. Results: In single-parent families, the quality of sibling relationship is low, positively correlated with Extraversion (R= .21) and positively correlated with Agreeableness (R= .37), Conscientiousness (R= .79), and Openness (R= .64) while negatively correlated with Neuroticism (R= -.46). In intact parent families sibling relationship is significantly negative correlated with Extraversion (R= -.65) and Agreeableness (R= -.47) while positively correlated with Neuroticism (R= .43) and Openness (R= .59) and low negatively correlated with Conscientiousness (R= -.22). Furthermore, results also revealed that significant difference had been found between quality of sibling relationship (T= 4.79) and personality traits i.e., Extraversion (T= 2.94), Agreeableness (T= 3.03), conscientiousness (T= 3.29) and Neuroticism (T= 4.12), while non-significant differences has been found on the variable of Agreeableness (T= 1.32). Conclusion: The research findings indicated that being raised by a single parent can positively impact the quality of relationships between siblings and individual personality traits compared to adults from intact families.